DARI PENGALAMAN MENJADI LITERASI: PENGUATAN LITERASI MENULIS DAN BERBICARA PADA SISWA SMP NEGERI 4 TAKALAR - Riana Multhazam; Nurul Fajriah Yahya; Khaerati; Andi Nur Veryani; Hamran (DEVELOPMENT: Journal of Community Engagement, 2026)
This study aims to describe the implementation of experiential learning in strengthening students' writing and speaking literacy at SMP Negeri 4 Takalar. The research employed a qualitative descriptive approach involving 32 eighth-grade students as participants. Data were collected through classroom observations, interviews, documentation, and assessment of students' literacy products. The learning process was designed by encouraging students to transform their personal experiences into written narratives and oral presentations. Data were analyzed through data reduction, data display, and conclusion drawing. The findings indicate that experience-based literacy activities significantly improved students' confidence, vocabulary mastery, idea organization, and communication skills. Students demonstrated greater motivation to write because the topics originated from their own experiences, making the writing process more meaningful and authentic. Furthermore, speaking activities based on students' written narratives enhanced fluency, confidence, and interaction during classroom discussions. The integration of writing and speaking literacy through experiential learning also fostered critical thinking, creativity, and reflective abilities. The study concludes that utilizing students' personal experiences as learning resources provides an effective strategy for strengthening literacy competencies and creating an engaging learning environment in junior secondary education.